2006
DOI: 10.1021/jo061060b
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Kinetic Resolution of Benzoins by Lipase−Metal Combo Catalysis

Abstract: The synthesis of some noncommercial racemic 1,2-diaryl-2-hydroxyethanones (benzoins) is described, optimizing the previously reported methodologies. In a further step, the kinetic resolution of these substrates is reported, obtaining conversions of around 50% and ee(p) higher than 99% in very short reaction times. As enzymatic catalyst, after screening of several enzymes, the lipase TL (from Pseudomonas stutzeri) was the most efficient, working in an organic solvent with a very low log P value, such as THF. Fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(49 citation statements)
references
References 53 publications
0
49
0
Order By: Relevance
“…An efficient DKR protocol for benzoins (1,2-diaryl-2-hydroxyethanones) was presented by Alcántara and coworkers in 2006 using Shvo's catalyst 1 for the racemization [78]. For the enzymatic resolution, Pseudomonas stutzeri lipase (Lipase TL) was used, giving the (S)-acylated products in excellent enantiomeric excesses (>99% ee) and with yields up to 90% (16).…”
Section: Dkr Of Secondary Alcoholsmentioning
confidence: 99%
“…An efficient DKR protocol for benzoins (1,2-diaryl-2-hydroxyethanones) was presented by Alcántara and coworkers in 2006 using Shvo's catalyst 1 for the racemization [78]. For the enzymatic resolution, Pseudomonas stutzeri lipase (Lipase TL) was used, giving the (S)-acylated products in excellent enantiomeric excesses (>99% ee) and with yields up to 90% (16).…”
Section: Dkr Of Secondary Alcoholsmentioning
confidence: 99%
“…Table 3 shows the excellent results obtained in the DKR of 1,2-diarylethanols [28] and benzoins. [36] Chemoenzymatic DKR is possible not only for simple aliphatic alcohols but also for those containing additional functional groups, such as alkenols, ethers, chlorohydrins, azido alcohols, amino alcohols, hydroxy esters, hydroxy phosphates, hydroxy sulfonates, and hydroxy amides (Table 4). In some cases, more than two functional groups were compatible with the conditions for DKR.…”
Section: Substrate Alcohols In Chemoenzymatic Dkrmentioning
confidence: 99%
“…Nevertheless, a systematic study on lipase-promoted transacylation (five different wild-type lipases were screened) concluded that Pseudomonas aeruginosa lipase is active and R selective toward bulky phenylalkanols. [6] Pseudomonas stutzeri lipase-catalyzed dynamic kinetic resolution (DKR) of 1,2-diarylethanols [7] and benzoins [8][9] (1,2-diaryl-2-hydroxyethanone structures) have been recently reported. In addition, substrates that have very bulky side groups flanking the carbonyl, such as phenyl isopropyl ketone, tend to be poor substrates for most known alcohol dehydrogenases.…”
Section: Introductionmentioning
confidence: 99%